Functional outcome of posterior-stabilized total knee replacement in women with primary osteoarthritis of the knee joint - V., Sudhakar M.; Thangaraja, Acksen; Basheer, Aysha Sabnam Mohammed (International Journal of Research in Orthopaedics, 2026)
Background: Osteoarthritis (OA) of the knee is highly prevalent in postmenopausal women, leading to significant pain and disability. Posterior-stabilized total knee replacement (PS TKR) replaces the posterior cruciate ligament (PCL) with a cam-post mechanism to restore stability and motion. However, data specifically addressing functional outcomes in women are limited. Methods: This prospective observational study was conducted in the Department of Orthopaedics, Dr. SMCSI Medical College Hospital, Karakonam, Kerala, from January 2023 to January 2025. 36 women patients with osteoarthritis knee who underwent PS TKR were included. Functional outcomes were assessed using KSS preoperatively and at 3 weeks, 6 weeks, 3 months, 6 months, and 1 year postoperatively. The relationship between BMI and KSS was analyzed. Results: The mean age of female patients was 63.3 years, and mean BMI was 29.4 kg/m². The mean preoperative KSS was 27.6, which improved to 92.3 at 1 year. At final follow-up, 90.5% of women achieved excellent and 9.5% good results. No significant difference in KSS was observed between BMI groups (p>0.05). Conclusions: Posterior-stabilized TKR offers excellent functional outcomes in women, independent of preoperative BMI. The procedure effectively alleviates pain and restores mobility in postmenopausal women with advanced osteoarthritis.